A matter of design and coupling: high indoor charging efficiencies with organic solar modules directly coupled to a sodium ion battery - Kin, Li Chung; Distler, Andreas; Astakhov, Oleksandr; Kone, Bakary; Kungl, Hans; Karl, André; Merdzhanova, Tsvetelina; Eichel, Rüdiger A.; Brabec, Christoph; Rau, Uwe (Journal of Materials Chemistry A, 2024)
To tackle the challenge of powering distributed autonomous indoor sensors and electronics, such as in the implementation of the internet of things (IOT), a high-efficiency solar module with integrated storage is a potential solution that offers a stable, reliable power source. For this, organic photovoltaics (OPV) are a promising candidate, delivering high efficiencies under indoor lighting, flexibility, scalability and low-cost designs via roll-to-roll manufacturing. Pairing an OPV device with batteries made from widely available sodium seems to be a viable strategy for achieving a low-cost, low-power, self-charging power source. PV devices can be coupled directly to batteries without power conditioning. Self-sustained operation and stable power output of this power harvester are achievable with proper voltage matching and scaling of both the PV and battery within the target range of operating conditions. We achieved a record indoor direct charging overall efficiency of an OPV and sodium ion battery of 13.1-14.4% over a wide range of LED illumination intensities of 150-15 000 lx.
CRIS-Team Scopus Importer:2024-11-01